Well-Posedness and Exponential Decay of the Thermoelastic Ful Von Kármán Beam with Second Sound and Discrete Delay Term - Bouzettouta, Lamine (Discontinuity, Nonlinearity, and Complexity, 2026)
The stabilization of one-dimensional thermoelastic system of full von Kármán beam with a delayed linear frictional damping is considered, where the heat fux is given by Cattaneo’s law. Under suitable assumption on the weight of the delay and that of frictional damping, we prove that the system is exponentially stable. The idea here, is to generalize some previous existing results by considering a delayed problem.